Main Features of Georgia’s Founding Council Elections - Darchashvili, Manana; Nishnianidze, Nino; Alaverdov, Emilia (European Scientific Journal, ESJ, 2020)
The elections of Georgia’s Democratic Republic founding council is a special event in the country’s political history, which is characterized by a number of special features, in both: within the country and at international scale. Consequently, the study of the past experiences and rethinking the political processes are very important and relevant. After the announcement of independence of Georgia (26th May 1918), the government had realized the necessity of the founding council’s elections. Therefore, the preparation of the election legislation began in the summer of 1918 and on November 22, the Parliament of Georgia had already approved the law – about “Regulations of the Founding Council Elections". In the article 119 the mentioned law was described every electoral issue and its regulations. In this process were involved almost all political subjects. It is important to highlight that by this regulation we can clearly see the democratic character of elections. According to the elections regulation, the elections would be held in proportional terms and there would be determined the rights of active and passive voters. It is important to note that at that period in Georgian reality the new regulations were already implemented on 14, 15, 16 February, 1919. The Central Election Committee registered the list of 15 Candidates and granted the election numbers to 15 political subjects. There were nominated 600 candidates, out of which 26 were women, and five of them became members of the founding council (it is noteworthy to point out that in some of modern democratic countries, woman was granted the right to vote much later). During the pre-election period the important issues of modern political parties are - the problems of program documents with their pre- election promises. It should be noted that even in the times of the founding council almost all election subjects had presented the electoral platform. It seems that the current problems are almost intersected. They were developing future reforms: emphasize human rights, labor rights, the establishment of general democracy, development of a peaceful environment and an active involvement in international cooperation. This is the reason of maintaining the importance of century long issues in modern society.